2023
DOI: 10.1021/acs.est.3c03884
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Ozone Formation Sensitivity during a Persistent Regional Ozone Episode in Northeastern China and Its Implication for a Control Strategy

Yujie Zhang,
Jian Gao,
Yujiao Zhu
et al.

Abstract: In recent years, the magnitude and frequency of regional ozone (O 3 ) episodes have increased in China. We combined ground-based measurements, observation-based model (OBM), and the Weather Research and Forecasting and Community Multiscale Air Quality (WRF−CMAQ) model to analyze a typical persistent O 3 episode that occurred across 88 cities in northeastern China during June 19−30, 2021. The meteorological conditions, particularly the wind convergence centers, played crucial roles in the evolution of O 3 pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Another study reported that a 50% reduction in NO x emissions can decrease PM 2.5 by about 14%, in the North China Plain . VOCs and NO x reduction should reduce by about 30% and 15% to achieve O 3 concentration reduction by 10% in reduction . However, controlling NO x emissions is partly counterproductive for O 3 improvement, as NO x reduction could shift the sensitivity of O 3 formation from the VOCs-limited regime to the NO x -limited regime. , A substantial reduction of NO x emissions led to an exacerbation of O 3 pollution in many urban areas. , Therefore, the effectiveness of NO x and VOCs control to effectively reduce PM 2.5 and O 3 depends not only on the decrease in absolute concentrations but also on changing their relative proportions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that a 50% reduction in NO x emissions can decrease PM 2.5 by about 14%, in the North China Plain . VOCs and NO x reduction should reduce by about 30% and 15% to achieve O 3 concentration reduction by 10% in reduction . However, controlling NO x emissions is partly counterproductive for O 3 improvement, as NO x reduction could shift the sensitivity of O 3 formation from the VOCs-limited regime to the NO x -limited regime. , A substantial reduction of NO x emissions led to an exacerbation of O 3 pollution in many urban areas. , Therefore, the effectiveness of NO x and VOCs control to effectively reduce PM 2.5 and O 3 depends not only on the decrease in absolute concentrations but also on changing their relative proportions.…”
Section: Introductionmentioning
confidence: 99%
“…However, controlling NO x emissions is partly counterproductive for O 3 improvement, as NO x reduction could shift the sensitivity of O 3 formation from the VOCs-limited regime to the NO x -limited regime. , A substantial reduction of NO x emissions led to an exacerbation of O 3 pollution in many urban areas. , Therefore, the effectiveness of NO x and VOCs control to effectively reduce PM 2.5 and O 3 depends not only on the decrease in absolute concentrations but also on changing their relative proportions. In addition, previous studies have determined that gaseous pollutants emitted from pollution sources are complex, due to the diversity of sources and their types. ,,, Overall, there has been limited research extending the study of gaseous precursors to pollution sources in the context of PM 2.5 and O 3 co-mitigation. To further advance the control of PM 2.5 and O 3 , a strategy that targets common pollution sources is needed, instead of focusing solely on NO x and VOCs.…”
Section: Introductionmentioning
confidence: 99%